2012
DOI: 10.1111/j.2042-7158.2012.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genistein, a natural soy isoflavone, on the pharmacokinetics and intestinal toxicity of irinotecan hydrochloride in rats

Abstract: Intravenous genistein was effective in ameliorating CPT-11-induced late-onset diarrhoea, by suppressing MRP2-mediated biliary excretion of CPT-11 and its metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…An animal model of irinotecan‐induced gastrointestinal damage was produced by intravenous administration of irinotecan at a dose of 60 mg/kg/day for 4 days, according to a previously reported protocol (Hu et al, ; Kurita et al, ; Sezer et al, ; Takasuna et al, , , , ; Yokooji et al, ) The villous atrophication, shortening, and loss observed in the small intestines of the irinotecan group on day 5 (Figure ) were consistent with previous observations (Gupta et al, ; Saltz et al, ; Takasuna et al, ); i.e., flattened villi and an increase in cell debris were seen in the rat cecum, jejunum, or ileum, together with reductions in body weight and food intake and changes in the stool score (Hu et al, ; Kurita et al, ; Takasuna et al, ). Therefore, the protocol used in this study successfully produced an animal model of irinotecan‐induced gastrointestinal damage.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…An animal model of irinotecan‐induced gastrointestinal damage was produced by intravenous administration of irinotecan at a dose of 60 mg/kg/day for 4 days, according to a previously reported protocol (Hu et al, ; Kurita et al, ; Sezer et al, ; Takasuna et al, , , , ; Yokooji et al, ) The villous atrophication, shortening, and loss observed in the small intestines of the irinotecan group on day 5 (Figure ) were consistent with previous observations (Gupta et al, ; Saltz et al, ; Takasuna et al, ); i.e., flattened villi and an increase in cell debris were seen in the rat cecum, jejunum, or ileum, together with reductions in body weight and food intake and changes in the stool score (Hu et al, ; Kurita et al, ; Takasuna et al, ). Therefore, the protocol used in this study successfully produced an animal model of irinotecan‐induced gastrointestinal damage.…”
Section: Discussionsupporting
confidence: 87%
“…An animal model of irinotecan-induced gastrointestinal damage was produced by intravenous administration of irinotecan at a dose of 60 mg/kg/day for 4 days, according to a previously reported protocol (Hu et al, 2006;Kurita et al, 2000;Sezer et al, 2009;Takasuna et al, 1995aTakasuna et al, , 1995bTakasuna et al, , 1996Takasuna et al, , 2006Yokooji et al, 2013) The villous atrophication, shortening, and loss observed in the small intestines of the irinotecan group on day 5 (Figure 1) were consistent with previous observations (Gupta et al, 1994;Saltz et al, 2000;Takasuna et al, 2006); i.e., flattened villi and an increase in cell debris were seen in the rat cecum, jejunum, or ileum, together with reductions in body weight and food intake and changes in the stool score (Hu et al, 2006;Kurita et al, 2000;Takasuna et al, 1996). Therefore, the T A B L E 2 PK parameters obtained after the oral administration of DABE or APAP and the intravenous administration of DAB or APAP As a result, the expression of P-gp was found to be significantly increased by oral 5-FU (Tsujii et al, 2018) along with the decrease in the BA value of DAB (Yotsumoto, Akiyoshi, Wada, Imaoka, & Ohtani, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not many rodent studies up to now evaluated the same biomarkers of liver function after exposure to IRI, but they reported generally similar results [ 36 , 81 , 82 , 83 ]. The existing literature on serum markers of rodent hepatocellular damage after exposure to THC is inconsistent [ 38 , 39 , 40 , 41 , 63 , 64 , 84 ].…”
Section: Resultsmentioning
confidence: 94%
“…SN-38 is inactivated and detoxified to SN-38 glucuronide (SN-38G) primarily through glucuronidation by hepatic uridine diphosphate (UDP)-glucuronosyltransferase 1A1 (UGT1A1). Most of CPT-11 and its metabolites are excreted into the intestinal lumen via bile, primarily mediated by multidrug resistance-associated protein-2 (MRP-2), breast cancer resistance protein (Bcrp), and P-glycoprotein (P-gp) (Yang et al, 2005 ; Bansal et al, 2009 ; Yokooji et al, 2013 ). The SN-38G that is excreted via bile is deconjugated by bacterial β-glucuronidase to SN-38, leading to the accumulation of SN-38 in the intestine.…”
Section: Introductionmentioning
confidence: 99%